2017
DOI: 10.1002/lt.24702
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil‐to‐lymphocyte ratio correlates with proinflammatory neutrophils and predicts death in low model for end‐stage liver disease patients with cirrhosis

Abstract: The Model for End-Stage Liver Disease (MELD) score has reduced accuracy for liver transplantation (LT) wait-list mortality when MELD ≤20. Neutrophil-to-lymphocyte ratio (NLR) is a biomarker associated with systemic inflammation and may predict cirrhotic decompensation and death. We aimed to evaluate the prognostic utility of high NLR (≥4) for liver-related death among low MELD patients listed for LT, controlling for stage of cirrhosis. In a nested case-control study of cirrhotic adults awaiting LT (February 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
73
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(83 citation statements)
references
References 37 publications
4
73
0
1
Order By: Relevance
“…9,23 The degree of neutrophilia may be reflective of the degree of inflammation but the relative lymphopenia may reflect a more subtle alteration of immune regulation. 7,10,24 In addition the degree of lymphopenia may also be reflective of sarcopenia as has been noted in other clinical contexts. 25 Protein energy malnutrition is a frequent finding in alcoholic hepatitis and is strongly related to outcome 26 and sarcopenia is increasingly recognised as an important factor in liver disease prognosis independent of traditional laboratory-based markers of liver function.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…9,23 The degree of neutrophilia may be reflective of the degree of inflammation but the relative lymphopenia may reflect a more subtle alteration of immune regulation. 7,10,24 In addition the degree of lymphopenia may also be reflective of sarcopenia as has been noted in other clinical contexts. 25 Protein energy malnutrition is a frequent finding in alcoholic hepatitis and is strongly related to outcome 26 and sarcopenia is increasingly recognised as an important factor in liver disease prognosis independent of traditional laboratory-based markers of liver function.…”
Section: Discussionmentioning
confidence: 82%
“…It is interesting to note that in these studies the prognostic value of NLR appears to be independent of standard scores of prognosis in liver disease such as the MELD and Child‐Turcotte‐Pugh scores . The degree of neutrophilia may be reflective of the degree of inflammation but the relative lymphopenia may reflect a more subtle alteration of immune regulation . In addition the degree of lymphopenia may also be reflective of sarcopenia as has been noted in other clinical contexts .…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Kalra et al showed NLR ≥ 4 was closely relevant to increased 90-day liver-related death in low MELD (MELD ≤ 20) outpatient subjects waiting for transplantation. 11 Intriguingly, a multicenter study by Rice et al revealed that NLR > 9 was associated with more than three-fold risk of 90-day mortality (HR 3.78, 95% CI 1.80-7.83) compared with the lowest quartile (NLR < 3). 12 The latter study recruited a unique population, who were predisposed to infection and development of ACLF, representing high mortality.…”
Section: Discussionmentioning
confidence: 97%
“…Our results are highly consistent with the growing body of literature implying NLR as a powerful indicator in cirrhotics. Kalra et al showed NLR ≥ 4 was closely relevant to increased 90‐day liver‐related death in low MELD (MELD ≤ 20) outpatient subjects waiting for transplantation . Intriguingly, a multicenter study by Rice et al revealed that NLR > 9 was associated with more than three‐fold risk of 90‐day mortality (HR 3.78, 95% CI 1.80‐7.83) compared with the lowest quartile (NLR < 3) .…”
Section: Discussionmentioning
confidence: 99%